The use of Webquest in blended EFL learning in Indonesia to improve students’ speaking skills - Amalia, Dian; Jati, Roko Patria (Institut Agama Islam Negeri IAIN Salatiga, 2018)
This study aimed to investigate the implementation of Webquest in a blended EFL (English as Foreign Language) learning context and the students’ speaking skills improvement dealing with it. A number of 21 students were involved in the classroom action research designed. This classroom action research focused on two pedagogical issues of the methodology as well as the students’ improvement of their speaking skills. The lesson plan including the test instruments was prepared in line with the proposed teaching model. To begin, the observation supported with field notes was executed to describe the teaching and learning process. We played the role of passive participant in this period. Subsequently, the students’ speaking skills were evaluated through oral test in which the results of pre-cycle test as well as after-cycles were analyzed using t-test. We found that there was a significant improvement on the students’ speaking skills in term of pronunciation, intonation, fluency, grammar and vocabulary within two cycles of action research. Thus, the implementation of Webquest as media in blended learning was successful to improve the students’ speaking skills.